The Effect of Stigmatization on Perceived Social Support and Quality of Life among Hiv/Aids Patients: A Gender-Based Analysis - Nadia Hameed; Prof. Dr. Erum Irshad (Journal of Management Practices, Humanities and Social Sciences, 2022)
The current study set out to find out how patients' views of social support and quality of life are impacted by stigma. Additionally, the quality of life of patients and gender variations in HIV stigma, social support, and other factors were compared. It was expected that male patients would do better than female patients on tests measuring stigma, perceived social support, and quality of life. A total of 269 HIV/AIDS patients, including those who were 18 years of age or older and either male (n=170) or female (n=99), made up the sample for the current study. Purposeful sampling was used to collect the sample from the Provincial AIDS Control Program (PACP) facility at the Hayatabad Medical Complex in Peshawar. The WHO Quality of Life Scale (WHOQOL, BREF), HIV Stigma Scale (HISS), and the Multidimensional Scale of Perceived Social Support (MSPSS) were administered separately. The data were analyzed using the independent t-test. The results showed a significant difference in the WHO quality of life score between HIV patients in men and women. However, there were no statistically significant differences between male and female HIV patients on the Multidimensional Scale of Perceived Social Support and the HIV stigma scale factors. In light of the research findings, further discoveries and potential long-term implications were examined at the conclusion.